Balanced Salt Solutions for Critically Ill Patients: Nonplused and Back to Basics. Issue 12 (December 2022) - Kopp, Brian J.; Lenney, Morgan; Erstad, Brian L.
Objectives: The purpose of this article is to summarize the results of major randomized controlled trials (RCTs) comparing clinical outcomes of critically ill patients treated with normal saline (NS) or balanced salt solutions (BSSs), address discordant results of these studies, and provide direction for future investigations. Data Sources: PubMed (2011 to January 2022) with bibliographies of retrieved articles searched for additional articles. Study Selection and Data Extraction: RCTs comparing NS and BSSs in critically ill adult patients. Data Synthesis: Recently published large RCTs comparing NS with BSSs in heterogeneous populations of intensive care unit patients did not find significant differences in mortality, despite positive findings in some end points in prior RCTs. However, there were a number of methodologic issues common to the RCTs including: varying study designs and end points, clinician discretion for the majority or all treatments other than the primary intervention fluid, heterogeneous patients with varying levels of acuity, and lack of power to investigate potential subgroup differences. In addition, there were problematic issues related to blinding and use of nonstudy fluids. Relevance to Patient Care and Clinical Practice: Intravenous fluids are a mainstay of supportive care for critically ill patients. Similar to the so-called crystalloid-colloid debate, there has been a long-standing debate among critical care clinicians and researchers concerning the preferred crystalloid solution, NS versus one of the available BSSs. Conclusions: Despite the recent publication of large multicenter RCTs, the preferred resuscitation fluid, NS or a BSS, for critically ill patients is still open for debate, although the available investigations do provide some direction for clinicians and for future investigations.